Ektraksi Ciri Citra Termogram Payudara Berbasis Dimensi Fraktal - Oky Dwi Nurhayati; Thomas Sri Widodo; Adhi Susanto; Maesadji Tjokronagoro (Faculty of Engineering, Universitas Gadjah Mada, 2010)
AbstractThe primary purpose of infrared thermography is the locating of thermal differences and anomalies. Infrared thermography can detect numerous conditions in which an anomaly is characterized by an increase or decrease in surface temperature. In this research, we specifically applied calculation of fractal dimension method to a total of20 thermograms of normal breasts as well as of those in advanced breast cancer. In addition standard image pre-processing were also used to enhance the detection capabilitity. Severalmethods in image processing which are pre-processing with canny edge detection, thresholding, calculation of fractal dimension use box-counting and Hausdorff dimension.The results of this research are shown that Hausdorff dimension in the normal thermogramshave range value 0,4 – 0,95 smaller than the advanced thermograms which have value more than 1,26.Finally this results show that the difference of fractal dimension can be used todistinguish between normal and advanced thermograms.Keywords: canny edge detection, thresholding, fractal dimension, box-counting, Hausdorff